THE GREAT HASAN BASRI WHO SHOOK THE WORLD - Kadamova Munisa Arslonbekovna; Scientific Supervisor: Shahlo Samanova (American Journals, 2024)
This article is about Hasan Basri, one of the great people who left an indelible mark in history. The life path of this person, the hardships he went through, how knowledgeable, philosopher, and wise he was. it is said that he devoted himself, that he did not spend even a single second of his life in vain. In order to return our "modern youth" who have gone to the internet and social networks and spend time away from real life in virtual life to real life, to warn them not to spend their time in vain activities, to introduce them to the intellectuals we know and don't know in history, how many of them reveals the meaning that he must grow up to be a generation worthy of his ancestors.
Keywords: Basra, Ibn Hajjaj, piety, wisdom, hilm, true charity, forgiveness, Jafari Sadiq, Jabir ibn Zayd, Umar ibn Khattab.